Consumer awareness and credibility factors of health claims on innovative meat products in a cross-sectional population study in the Netherlands. (December 2016) - Strijbos, C.; Schluck, M.; Bisschop, J.; Bui, T.; de Jong, I.; van Leeuwen, M.; von Tottleben, M.; van Breda, S.G.
Highlights: 88.5% of the respondents accepts meat products combined with plant extracts. Sex, age nor weekly meat consumption is associated with credibility of health claims. Lower educational levels perceive health claims as more credible. The Dutch Gastro-Intestinal Foundation is considered the most trust worthy promoter. A health related magazine is considered as the most trust worthy platform. Abstract: Meat consumption-associated cancer risks relating to the preservative nitrate are receiving considerable attention. Consequently, innovative meat products are being developed with no or reduced nitrate levels. For example, phytochemicals are currently under investigation for their potential to replace nitrate in meat. Consumers are becoming more aware of health aspects of consumed foods, a trend which is accompanied by an increase in health claims on food products. However, consumer acceptance of a health claim is dependent on consumer credibility of the claim. In order to produce a health claim, perceived credible by consumers, it should be known which factors influence consumer credibility. This pilot study investigated the extent to which consumers perceive health claims on innovative meat products credible and which factors influence this credibility. By means of a questionnaire distributed amongst 1010 Dutch participants representative of the Dutch population, factors like health claim promoters, media platforms, and the phrasing of the proposed health claim were investigated. Main results are that the majority of consumers indicates meat products with phytochemicals as acceptable. Promotion by a national health foundation is perceived as credible, and health magazines are perceived as a credible media platform. This study found that neither weekly meat consumption, sex, nor age have effect on the consumer credibility of certain health claims, but that educational level does.